Food demand and meal size in mice with single or combined disruption of melanocortin type 3 and 4 receptors - Atalayer, Deniz (American Physiological Society, 2010)
Mice with homozygous genetic disruption of the melanocortin-4 receptor gene (MC4R−/−) are known to be hyperphagic and become obese, while those with disruption of the melanocortin-3 receptor gene (MC3R−/−) do not become markedly obese. The contribution of MC3R signaling in energy homeostasis remains little studied. In the present work, we compare MC3R−/− mice with wild-type (WT), MC4R−/−, and mice bearing disruption of both genes (double knockout, DKO) on select feeding and neuroanatomical dimensions. DKO mice were significantly more obese than MC4R−/−, whereas MC3R−/− weighed the same as WT. In a food demand protocol, DKO and MC4R−/− were hyperphagic at low unit costs for food, due primarily to increased meal size. However, at higher costs, their intake dropped below that of WT and MC3R−/−, indicating increased elasticity of food demand. To determine whether this higher elasticity was due to either the genotype or to the obese phenotype, the same food demand protocol was conducted in dietary obese C57BL6 mice. They showed similar elasticity to lean mice, suggesting that the effect is of genotypic origin. To assess whether the increased meal size in MC4R−/− and DKO might be due to reduced CCK signaling, we examined the acute anorectic effect of peripherally administered CCK and subsequently the induction of c-Fos immunoreactivity in select brain regions. The anorectic effect of CCK was comparable in MC4R−/− , DKO, and WT, but it was unexpectedly absent in MC3R−/−. CCK-induced c-Fos was lower in the paraventricular nucleus in MC3R−/− than the other genotypes. These data are discussed in terms of demand functions for food intake, MC receptors involved in feeding, and their relation to actions of gut hormones, such as CCK, and to obesity.